2018
DOI: 10.3390/ijerph15030520
|View full text |Cite
|
Sign up to set email alerts
|

Bread and Shoulders: Reversing the Downward Spiral, a Qualitative Analyses of the Effects of a Housing First-Type Program in France

Abstract: This paper is a qualitative analysis of the effects of accompagnement, a support framework, on recovery trajectories of people with long-term homelessness and severe psychiatric disorders during 24 months in a Housing First-type program in France. A comprehensive methodology based on grounded theory was used to construct an interview guide, conduct multiple interviews with 35 Housing First participants sampled for heterogeneity, and produce memos on their trajectories before and after entering the program base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
(58 reference statements)
2
9
0
Order By: Relevance
“…Importantly, Epel et al (1999) recognized that although important as a correlate of attempted extrication from homelessness, self-efficacy was not correlated with successful extrication, given local housing crises. Our study is also consistent with previous findings that hope increases among formerly homeless adults and among formerly homeless youth when they are housed (Kidd et al, 2016; Rhenter et al, 2018). A Vancouver-based study examining the effects of housing on hope found an initial decrease in hope among formerly homeless youth due to demoralization, but a longer term increase in hope among those youth who later experienced success (Kidd et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, Epel et al (1999) recognized that although important as a correlate of attempted extrication from homelessness, self-efficacy was not correlated with successful extrication, given local housing crises. Our study is also consistent with previous findings that hope increases among formerly homeless adults and among formerly homeless youth when they are housed (Kidd et al, 2016; Rhenter et al, 2018). A Vancouver-based study examining the effects of housing on hope found an initial decrease in hope among formerly homeless youth due to demoralization, but a longer term increase in hope among those youth who later experienced success (Kidd et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…There were 16 eligible studies in this domain, nine of which were quantitative [28][29][30][31][32][33][34][35][36] and seven qualitative [37][38][39][40][41][42][43] Full-text articles excluded (N=184) ies were conducted in eight different countries: six in Canada 28,[35][36][37]42,43 , three in the UK 31,33,34 , two in the US 30,41 , and one each in Australia 32 , France 39 , India 38 , the Netherlands 29 and Norway 40 .…”
Section: Supported Accommodation (See Table 1)mentioning
confidence: 99%
“…Participants in the HF group, with the support of the team, applied for housing allowances, welfare and disability allowances. This explains the simultaneous increase in welfare benefits over the 2 years of follow up (Rhenter et al ., 2018). Costs of justice were not impacted by the intervention due to very small sample size to capture an effect on this service use.…”
Section: Discussionmentioning
confidence: 99%